Beam-ACO for the Lock Chamber Arrangement - Liu, Ruijie; Li, Lin; Zhai, Yue; Sun, Jianyan (2020 IEEE 3rd International Conference on Computer and Communication Engineering Technology (CCET), 2020)
With the development of waterway transportation in China, there are many problems to be solved in waterway transportation, among which the lock congestion is a common problem in waterway transportation in China, especially in some dams with frequent waterway transportation. Water transport congestion will not only affect the normal travel of water transport ships, but also cause certain economic losses to ships. Water transport lock congestion has seriously hindered the development of water transport in China. This paper mainly analyzed the current situation and problems of waterway transportation, and established a hybridizing ant colony optimization with beam search method for the lock chamber arrangement optimization to alleviate traffic congestion from the actual needs, implemented corresponding algorithm through further design, and tested the validity of it through the Three Gorges-Gezhou Dam lock chamber arrangement and the Qingyuan Water Conservancy lock chamber arrangement. The experimental results showed that the hybridizing ant colony optimization with beam search method is effective in application of the lock chamber arrangement for the improving the ship lock practical navigation capacity.